FEMINISM IN KAKAWIN N?TIS?STRA - Sukatha, I Nyoman (e-Journal of Linguistics; Vol. 9. Juli 2015 No. 2)
Kakawin Nîtis?stra is a type of non-narartive old Javanese poetry . It contains moral teaching and governing politics. One of the teachings is the ethic of students in learning which is necessary to be adopted. The ethic states that during learning period  students  are not allowed to get married.The way of  the implementation of  the ethic is  through disgracing  women, so it as negative meaning. The theory applied in analyzing the vision of Nîtis?stra towards women is the theory of literary deconstruction. Literary deconstruction states that there is an implicit meaning within the existence of meaning in a piece of literary work. In order to reveal the implicit meaning, the literary work needs to be open into its parts and then deconstructed. Nîtis?stra reveals that women has their own weaknesses such: stupid, the way of their thinking is hard to be followed by men, dishonest,the cause of all misery, and even it can be as the cause of a war or a world destruction. So it gives negative judgement. Nîtis?stra`s judgment as stated above signals there is an implicit meaning in it.  It is the meaning of “fear and obedient” with the existence of women.
Keywords: Feminisme, Kakawin and Nîtis?stra